Structural and metamorphic geochronology of the Torngat Orogen in the North River-Nutak transect area, Labrador: Preliminary results of U-Pb dating - Bertrand, Jean-Michel; Van Kranendonk, Martin; Hanmer, Simon; Roddick, J.; Ermanovics, Ingo (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1990)
Summary Preliminary precise age determinations of tectonic and metamorphic events across a transect of the Torngat Orogen have shown atime-span of 80 million years between the oldest synmetamorphic intrusions and the latest uplift of the orogen. Two tectonothermal peaks have been determined at 1844 Ma (eastern and central part of the transect) and at 1826 Ma (western part of the transect).